Assessment of the efficacy of digital panoramic radiographs in analyzing changes in bone mineral density in postmenopausal women - Lisa Elizabeth Jacob; Kailasam Subramanian; Srividhya Srinivasan; Meenakshi Krishnan; Anand Krishnan; Anju Mathew (Journal of Family Medicine and Primary Care, 2022)
Introduction: Osteoporosis is described by the World Health Organization (WHO) as a 'progressive systemic skeletal disease characterized by low bone mass, microarchitectural deterioration of bone tissue, a consequent increase in bone fragility, and susceptibility to fracture. The maxilla and mandible are also affected by osteoporotic changes and these may be visualized using an Orthopantomogram. Aims and Objectives: To determine the radiomorphometric indices in the digital orthopantomograms, to determine the bone mineral density (BMD) of the lumbar spine and femur using DXA (Dual-Energy X-ray Absorptiometry) scan, to compare the measured indices between the BMD categories and to assess the correlation of these indices with the measured BMD. Materials and Methods: The study population included 30 postmenopausal female patients. The BMD was measured at the lumbar spine and at the femur and the patients were divided into three groups of 10 subjects based on their BMD status (normal, osteopenia, and osteoporosis). The patients were then subjected to panoramic radiography and four panoramic indices were assessed (simple visual estimation, mandibular cortical index, mental index, and antegonial index). The measured indices were compared between the three BMD categories. The correlation between the indices and the BMD was also observed. Results: The measured indices showed significant difference among the BMD categories. The quantitative indices also demonstrated a positive correlation with the measured BMD of the lumbar spine and the femur. Conclusion: Panoramic radiography may be used as a diagnostic tool for screening and identifying subjects who are likely to have osteoporosis.